2019
DOI: 10.4236/ojog.2019.94042
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators to Immediate Post Partum Intra Uterine Contraceptive Device Uptake among Mothers Delivering in Meru Hospital

Abstract: Family planning allows people to attain their desired number of children and determine the spacing of pregnancies. It is important to promote uptake of family planning services because it is one of the four pillars of the Safe Motherhood Initiative to reduce maternal death in developing countries. It is also enshrined in health related Sustainable Development Goals. Post Partum Intra Uterine Contraceptive Device (PPIUCD) is the oldest methods of family planning. During the ancient times, foreign bodies like st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Lack of knowledge on available health services such as family planning has also been evident among women in Meru community. 15,16 These findings were in agreement with the findings of a study on the health care seeking behaviors in BPH which exhibited that majority of patients (71.3%) reported that disturbing urinary symptoms were the principal reason why they sought medical advice. Therefore the researcher rejected the hypothesis which stated that there are no patient related factors influencing health seeking practices among men with LUTS.…”
Section: Patient Related Factors and Health Seeking Practicessupporting
confidence: 89%
“…Lack of knowledge on available health services such as family planning has also been evident among women in Meru community. 15,16 These findings were in agreement with the findings of a study on the health care seeking behaviors in BPH which exhibited that majority of patients (71.3%) reported that disturbing urinary symptoms were the principal reason why they sought medical advice. Therefore the researcher rejected the hypothesis which stated that there are no patient related factors influencing health seeking practices among men with LUTS.…”
Section: Patient Related Factors and Health Seeking Practicessupporting
confidence: 89%
“…14 Attitude of healthcare providers has been a factor in influencing health seeking behavoiurs and uptake of healthcare services. 15,16 Telehealth services can be provided to improve health seeking behavior in areas far from health facilities. 17…”
Section: Health Seeking Behaviourmentioning
confidence: 99%
“…Despite the many advantages of PPIUCD as a method of family planning, in many parts of world it is not as popular as pills, implants and depo provera. [9][10]…”
Section: Introductionmentioning
confidence: 99%